Operation Valuation: Teaching Pricing Concepts in an Experiential Environment. (August 2016) - Mills, Adam J.; Treen, Emily
Although marketing education has seen a dramatic shift toward hands-on, experiential learning in recent years, the teaching of pricing has fallen behind complementary elements of the marketing mix in pedagogical execution. Although the teaching of pricing has shifted focus from economic-based models to value-based pricing in theory, available pedagogical tools for teaching value-based pricing are scarce. This article proposes and outlines an experiential class assignment that engages students in a real-world, applied, market exchange environment. While avoiding the inherent risks of using actual money for transactions, this assignment enables students to explore the consumer motivations and perceptions of value central to value-based pricing.